Melting-pot modernism - Wilson, Sarah, 1973- (Cornell University Press, 2010)
"Melting-Pot Modernism is an intelligent and beautifully written examination of the 'melting pot' as taken up in the work of four modernist writers. For Henry James, James Weldon Johnson, Willa Cather, and Gertrude Stein, questions of novelty and difference familiar to the immigration, assimilation, and nativist debates were likewise aesthetic concerns for problems of form, the self, and one's relation to the past and to others. Sarah Wilson's readings of individual texts are ingenious and illuminating; her argument is fruitfully grounded in solid historical understanding of the authors' lives and of contemporaneous debates on immigration."--Christopher Douglas, University of Victoria, author of A Genealogy of Literary Multiculturalism.